PENENTUAN MASSA JENIS OLI SECARA SEDERHANA DENGAN HUKUM ARCHIMEDES - Gideon, Samuel; Tarigan, Enda Rasilta (Faculty of Science and Education, UIN Walisongo Semarang, 2020)
The most commonly used method for measuring the density of liquids is based on Archimedes' law. Lubricating oil generally has a defined density standard to show the quality of the oil. The purpose of this study is to determine oil density simply by applying Archimedes' law. This research was conducted in three steps. First, the measurement of the empty pycnometer. Second, the measurement of the pycnometer mass containing distilled water and oil. Third, measurement of copper mass in the medium of air, distilled water and oil. From the results of measurements and calculations, the obtained density of distilled water is (0.995 ± 3,582 x 10-4) gr/cm3 whose value is very close to the value of 1 gr/cm3 so that the distilled water used in this study is suitable as a reference/standard in finding volume copper; oil density is (0.868 ± 2.14 x 10-3) gr/cm3 whose value is very close to the value of oil density measured and calculated with a pycnometer of (0.875 ± 4.637 x 10-4) gr/cm3.